Attentional control mediates the relationship between social anhedonia and social impairment - Tully, Laura M.; Lincoln, Sarah Hope; Hooker, Christine I. (Frontiers in Psychology, 2014)
Social anhedonia, a traitlike disinterest in social contact and diminished capacity to experience pleasure from social interactions, is consistently associated with social impairments in both healthy and clinical populations. However, the mechanisms underlying the relationship between social anhedonia and social impairment are poorly understood. Attentional control, selecting and focusing on relevant information and inhibiting irrelevant, may be one such mechanism. We examined individual differences in social anhedonia, attentional control, and social impairment in 108 healthy adults. High social anhedonia related to low attentional control and high social impairment. Moreover, attentional control mediated the relationship between social anhedonia and social impairment, establishing attentional control as one mechanism underlying aberrations in the fundamental human need for social contact. Although both attentional deficits and social impairment have been separately noted in social anhedonia, the relationship between social anhedonia, attentional control and social impairment in this non-clinical sample reflects a novel contribution.